PENGARUH FREKUENSI PEMBERIAN PAKAN TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN BENIH KERAPU CANTANG (Epinephelus fuscoguttatus >< lanceolatus) - Yuftahul Azis; Subandiyono Subandiyono; Suminto Suminto (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2021)
Cantang grouper juveniles are fish that have a habit of being cannibalistic if the feed needs are not met, this tends to occur at the juveniles stage. So that in the maintenance of cantang grouper juveniles, it is necessary to provide the right frequency of feeding, because with the right frequency of feeding it will be able to meet the nutritional needs of the cantang grouper juveniles which are expected to increase the growth and survival of the grouper juveniles. The aim of this study was to examine the effect of feeding frequency on the growth and survival of Cantang grouper juveniles (Epinephelus fuscoguttatus> <lanceolatus). This study consisted of four treatments, namely treatment A (3 times a day), B (4 times a day), C (5 times a day) and D (6 times a day). Each treatment had three replications. The method used in this research is experimental research with a completely randomized design (CRD). Some of the variables measured were the level of feed consumption (TKP), feed utilization efficiency (EPP), protein efficiency ratio (PER), and relative growth rate (RGR), survival rate (SR). The results showed that feeding had a significant effect on the variable rate of feed consumption (TKP), feed utilization efficiency (EPP), protein efficiency ratio (PER), and relative growth rate (RGR), survival rate (SR), which was known as treatment. D (6 times a day) is the best treatment with TKP results of 58.37 ± 1.89 grams, EPP of 87.57 ± 2.46%, PER of 1.75 ± 0.05%, RGR of 5.14 ± 0.20%, and the highest SR was 96.67 ± 2.89%. Based on the results of this study, it can be concluded that treatment D in the form of feeding with a frequency of 6 times a day is the best treatment in increasing the growth and survival rate of Cantang grouper juveniles.